The influence of emotional intelligence on tacit knowledge sharing in service organizations - Othman, Abdul Kadir; Abdullah, Hazman Shah (2008)
The challenge of knowledge management is to facilitate tacit knowledge sharing (TKS) so that it is extracted into organizational memory.In team environment, trust in crucial to TKS. The road to a trusting relationship is marked by inter-personal understanding and empathic communication between members. Emotional intelligence (EI) as the ability to control one’s and other’s emotions will facilitate the sharing of high value tacit knowledge of work and clients among team members.The role of EI in promoting TKS will be constrained by the type of service environment i.e. professional, service and mass.This paper offers several testable propositions to explain the influence EI on TKS.